Informal Coercion Experienced by Adolescents – A systematic literature review - Överlund, Tiina (My University, 2025)
Adolescents are a developmentally vulnerable group in mental health care, yet their experiences of informal coercion, referring to non-legislated pressures used to influence decisions, remain underexplored. Previous research has focused on adult perspectives, leaving a gap in understanding how adolescents experience such practices. The aim of this master´s thesis was to synthesize qualitative evidence on the forms and consequences of informal coercion as experienced by adolescents in mental health care. This thesis was conducted as a systematic literature review and a scientific research article has been produced as part of the thesis. The review followed PRISMA guidelines and was registered in PROSPERO. Data were identified through systematic searches of seven databases (PubMed, CINAHL, PsycINFO, EMBASE, Scopus, Web of Science, and the Cochrane Library) and manual searching. A total of 5039 records were screened using predefined eligibility criteria, resulting in twelve peer-reviewed articles being included. Data were analysed using qualitative content analysis guided by a framework of previously identified forms of informal coercion. Informal coercion emerged as a multidimensional and relational phenomenon influencing adolescents’ possibilities for participation in care. Adolescents experienced pressure to accept treatment, exclusion from decision making, silencing, and restrictions justified by institutional routines. In some cases, pressure was accompanied by threats or disciplinary control. These practices undermined adolescents’ autonomy, trust, and sense of agency, and were associated with emotional distress and resistant coping, such as compliance, concealment, or overt opposition. Some adolescents, however, perceived structured pressure as protective or supportive. Informal coercion is present and consequential in adolescent mental health care. Existing adult-based conceptualizations may overlook its relational and subtle nature. Ethical concerns arise from the mismatch between adolescents’ developmental need for autonomy and the restrictive care environments. Bringing adolescents’ exeriences to the forefront is essential for developing ethically sound, participatory, and developmentally appropriate mental health care. Future research should further explore how clinical environments, relational practices, and organizational cultures could support adolescents' participation in treatment without relying on coercive influence. Clinical practice must move towards approaches where adolescents are not only listened to but are systematically included as partners in decisions concerning their care.

Nuoret ovat kehityksellisesti haavoittuva ryhmä mielenterveyshoidossa, mutta heidän kokemuksensa päätöksentekoon kohdistuvasta, lakiin perustumattomasta epävirallisesta painostuksesta ovat edelleen vähän tutkittuja. Aiempi tutkimus on keskittynyt aikuisten näkökulmiin, jättäen merkittävän tiedonaukon siitä, miten nuoret itse kokevat nämä käytännöt. Tämän pro gradu -tutkielman tavoitteena oli koota ja jäsentää laadullista tutkimusnäyttöä siitä, millaisia epämuodollisen pakon muotoja nuoret kokevat mielenterveyden hoidossa ja millaisia seurauksia näillä kokemuksilla on. Tutkielma toteutettiin systemaattisena kirjallisuuskatsauksena ja osana tutkielmaa laadittiin tieteellinen tutkimusartikkeli. Katsaus noudatti PRISMA-ohjeistusta ja se rekisteröitiin PROSPERO-tietokantaan. Aineisto kerättiin systemaattisen tietokantahaun avulla seitsemästä tietokannasta (PubMed, CINAHL, PsycINFO, EMBASE, Scopus, Web of Science ja Cochrane Library) sekä manuaalisen haun kautta. Ennalta määriteltyjen sisäänottokriteerien avulla seulottiin yhteensä 5039 viitettä, joista lopulliseen aineistoon sisältyi kaksitoista vertaisarvioitua artikkelia. Aineisto analysoitiin laadullisen sisällönanalyysin menetelmin hyödyntäen aiemmin tunnistettuihin epävirallisen pakon muotoihin perustuvaa analyysirunkoa. Tulosten perusteella epämuodollinen pakko näyttäytyy moniulotteisena ja vuorovaikutussuhteissa rakentuvana ilmiönä, joka vaikuttaa nuorten mahdollisuuksiin osallistua hoitoonsa. Nuoret kuvasivat hoitoon suostumiseen kohdistuvaa painetta, poissulkemista päätöksenteosta, hiljentämistä sekä institutionaalisiin rutiineihin perustuvia rajoituksia. Joissakin tapauksissa painostukseen liittyi uhkailua tai kurinpidollisia toimia. Kokemukset heikensivät nuorten autonomiaa, luottamusta ja toimijuuden tunnetta sekä olivat yhteydessä emotionaaliseen kuormittumiseen ja erilaisten selviytymiskeinojen käyttöön, kuten myötäilyyn, asioiden salaamiseen tai avoimeen vastarintaan. Osa nuorista koki ympäristön rakenteisiin liittyvän paineen kuitenkin myös suojaavana tai hoitoa tukevana. Epämuodollinen pakko on läsnä ja merkityksellinen ilmiö nuorten mielenterveyshoidossa. Aikuisten näkökulmista kehitetyt käsitteelliset mallit eivät välttämättä kuitenkaan tavoita epävirallisen pakon hienovaraista ja vuorovaikutuksessa rakentuvaa luonnetta, ja tämän tutkielman tulokset tuovat esiin eettisen ristiriidan nuorten autonomiatarpeen ja hoitoympäristöjen rajoittavien käytäntöjen välillä. Nuorten kokemusten näkyväksi tekeminen on välttämätöntä, jotta hoitoa voidaan kehittää eettisesti kestäväksi, osallistavaksi ja nuorten kehitysvaiheeseen sopivaksi. Jatkossa tutkimuksen tulisi tarkastella, miten hoitoympäristöt, vuorovaikutustavat ja organisaatiokulttuurit voivat tukea nuorten osallisuutta ilman pakottavia vaikutuskeinoja.
Keywords: adolescent, informal coercion, mental health care, systematic review